Single fusion events at polarized liquid–liquid interfaces - Laborda, E; Molina, A; Fernández Espín, V; Martínez-Ortiz, F; García de la Torre, J; Compton, R (Wiley, 2016)
A new electrochemical framework for tracking individual soft particles in solution and monitoring their fusion with polarized liquid–liquid interfaces is reported. The physicochemical principle lies in the interfacial transfer of an ionic probe confined in the particles dispersed in solution and that is released upon their collision and fusion with the fluid interface. As a proof-of-concept, spike-like transients of a stochastic nature are reported in the current–time response of 1,2-dichloroethane(DCE)|water(W) submilli-interfaces after injection of DCE-in-W emulsions. The sign and potential dependence of the spikes reflect the charge and lipophilicity of the ionic load of the droplets. A comparison with dynamic light scattering measurements indicates that each spike is associated with the collision of a single sub-picoliter droplet. This opens a new framework for the study of single fusion events at the micro- and nanoscale and of ion transport across biomimetic soft interfaces.